The Influence of Corporate Governance and Audit Quality on Financial Performance with Earnings Management as a Mediating Variable (Case Study on Manufacturing Companies Listed on the IDX) (Dhana, 2025)
This study aims to determine the effect of corporate governance and audit quality on financial performance with earnings management as a mediating variable. The population of this study is manufacturing companies listed on the IDX in 2020-2023. The sample of this study uses a purposive sampling technique with a total final sample of 175 manufacturing companies. This research method uses a quantitative method with secondary data in the form of company annual reports. The results of the study indicate that corporate governance has a positive effect on financial performance. Audit quality has a positive effect on financial performance. Earnings management has a positive effect on financial performance. Corporate governance has a negative effect on earnings management. Audit quality has a positive effect on earnings management. Earnings management is able to partially mediate the effect of corporate governance and audit quality on financial performance.